Design and Simulation of a Robotic System Integrated With Flywheel Energy Storage for Power Outage Resilience - Celikel, Resat; Aydogmus, Omur; Yilmaz, Musa (Wiley, 2025)
In industrial robotics, it is crucial to ensure the completion of ongoing processes in the event of a power outage. In this study, a robotic system integrated with a solar panel production system was designed using the ABB RobotStudio program. The energy consumed by the robot during a single cycle was calculated within the same software. Additionally, the energy consumption of the motors in the belt and table system was estimated based on real-world systems. To address power interruptions, a flywheel energy storage system (FESS) was designed to ensure the continuation of operations. The FESS is capable of supplying the required energy even at the initial start of the robotic system's mission. A notable aspect of this setup is that the drive systems of the motors operate at 800 V. When functioning as a generator, the FESS delivers this voltage to the DC link of the robotic system by acting as a boost converter. The FESS utilizes a high-speed BLDC motor, and an LC filter is placed between the motor and the inverter. When the motor operates in generator mode, the filter components enable its use as a boost converter. During a single process cycle, the system's speed ranges between 4500 and 3700 r/s. The FESS system was simulated in the MATLAB/Simulink environment, and the results are presented in graphical form.
Keywords: boost converter; energy storage; flywheel; robotic system